Evidence for an unidentified non-photochemical ground-level source of formaldehyde in the Po Valley with potential implications for ozone production - Jennifer Kaiser; Glenn M. Wolfe; Bohn, Birger; Broch, Sebastian; Fuchs, Hendrik; Ganzeveld, L. N.; Sebastian Gomm; Rolf Haeseler; Hofzumahaus, Andreas; Holland, Frank; J. Jäeger; Xin Li; et al. (Atmospheric Chemistry and Physics, 2015)
Ozone concentrations in the Po Valley of northern Italy often exceed international regulations. As both a source of radicals and an intermediate in the oxidation of most volatile organic compounds (VOCs), formaldehyde (HCHO) is a useful tracer for the oxidative processing of hydrocarbons that leads to ozone production. We investigate the sources of HCHO in the Po Valley using vertical profile measurements acquired from the airship Zeppelin NT over an agricultural region during the PEGASOS 2012 campaign. Using a 1-D model, the total VOC oxidation rate is examined and discussed in the context of formaldehyde and ozone production in the early morning. While model and measurement discrepancies in OH reactivity are small (on average 3.4 ± 13%), HCHO concentrations are underestimated by as much as 1.5 ppb (45%) in the convective mixed layer. A similar underestimate in HCHO was seen in the 2002–2003 FORMAT Po Valley measurements, though the additional source of HCHO was not identified. Oxidation of unmeasured VOC precursors cannot explain the missing HCHO source, as measured OH reactivity is explained by measured VOCs and their calculated oxidation products. We conclude that local direct emissions from agricultural land are the most likely source of missing HCHO. Model calculations demonstrate that radicals from degradation of this non-photochemical HCHO source increase model ozone production rates by as much as 0.6 ppb h−1 (12%) before noon.